Colloidal synthesis of VSe2 single-layer nanosheets as novel electrocatalysts for the hydrogen evolution reaction. Issue 59 (17th June 2016) - Zhao, Wenwen; Dong, Bohua; Guo, Zenglong; Su, Ge; Gao, Rongjie; Wang, Wei; Cao, Lixin
Abstract : We present a one-pot colloidal route to synthesize VSe2, a new type of metallic single-layer nanosheet. Abstract : We present a one-pot colloidal route to synthesize VSe2, a new type of metallic single-layer nanosheet. The ∼0.4 nm thick VSe2 single-layer nanosheets possess extraordinary electrocatalytic hydrogen evolution reaction (HER) performance with a low onset overpotential of 108 mV, a small Tafel slope of 88 mV per decade, and an exceptional overpotential of 206 mV at a current density of 10 mA cm −2 .